Konsep Pendidikan Akal pada Kurikulum Pendidikan Agama Islam (PAI) Tingkat Sekolah Dasar (SD) - Azni, Selly Rachmi; M. Yunus, Badruzzaman; Fathurrohman, Asep Ahmad (Edukasi: Journal of Educational Research, 2022)
This paper discusses the concept of intellectual education and how to implement it in the PAI curriculum at the Elementary School (SD) level. The research procedure used in this study is library research, and uses qualitative methods. The data collection techniques in this study use documentation techniques. Meanwhile, in analyzing the data, the author uses content analysis techniques. This study found that the concept of Intellectual Education in the PAI curriculum is an idea or idea that is structured in a curriculum document as a guide for educators in guiding, training and forming critical, logical, systematic and rational thinking skills, so that students develop into human beings who believe, are pious. , and have good character. The continuity of the PAI curriculum in containing the concept of reason education as an important part of character educators in the KBK, KTSP, and 2013 Curriculum, all of which are interconnected in their development and complement each other.